The effectiveness of calcium hydroxide paste mixed with 2% chlorhexidine solution against Candida albicans-infected human roots: An ex vivo study - Fahd Alsalleeh; Amani Almohaimeed; Anfal Almoqbel; Ziyad Allahem (Wolters Kluwer Medknow Publications, 2019)
It is known that Candida albicans is involved in the etiology of persistent periradicular lesions. Aims: The aim of this study was to determine the antifungal activity of calcium hydroxide (Ca[OH]2), paste (Ultradent Products Inc., South Jordan, UT, USA) mixed with 2% chlorhexidine against C. albicans. Subjects and Methods: Fifty extracted human single-rooted teeth were selected. The teeth were standardized and instrumented with K3™ Nickel-Titanium rotary files (Kerr Dental). Teeth were then infected with C. albicans, except negative controls. After 7 days, teeth were randomly divided into the following groups according to intracanal medicament protocols (n = 10): Ca(OH)2 mixed with 2% chlorhexidine, Ca(OH)2 mixed with normal saline, Ca(OH)2 alone, or 2% chlorhexidine alone. Normal saline alone was used as positive controls. All teeth were incubated at 37°C and 100% humidity for a week. C. albicans growth was recorded. Pairwise comparison and Tukey's analysis of mean differences were conducted with the significance level set at the 0.05 level. Results: All samples of the positive controls, Ca(OH)2 alone and Ca(OH)2 mixed with the saline groups showed C. albicans growth (100%). Ca(OH)2 mixed with chlorhexidine showed 70% growth, whereas chlorhexidine alone group showed 60% growth. The negative controls had no growth. Conclusions: A mixture of Ca(OH)2 and 2% chlorhexidine had better antifungal activity against C. albicans in human-extracted teeth compared to that of Ca(OH)2 alone.